Integrated resource-saving waterconsumption and water-disposal system of glass-work - O. A. Usanova; M. V. Bushuev; A. V. Nevsky; V. A. Sharnin (Тонкие химические технологии)
The methodology of designing of water resource-saving chemical process of glass works has been proposed. The basis of it is thermodynamic approach to analysis and synthesis (designing) of processes (the application of thermodynamic exergy method). The proposed methodology was approved by water chemical process designing of large-scale glass enterprises (production of glass fiber, glass cloth, hardened glass).